If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 1 = 3x + -7 Reorder the terms: 1 + 9x = 3x + -7 Reorder the terms: 1 + 9x = -7 + 3x Solving 1 + 9x = -7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 1 + 9x + -3x = -7 + 3x + -3x Combine like terms: 9x + -3x = 6x 1 + 6x = -7 + 3x + -3x Combine like terms: 3x + -3x = 0 1 + 6x = -7 + 0 1 + 6x = -7 Add '-1' to each side of the equation. 1 + -1 + 6x = -7 + -1 Combine like terms: 1 + -1 = 0 0 + 6x = -7 + -1 6x = -7 + -1 Combine like terms: -7 + -1 = -8 6x = -8 Divide each side by '6'. x = -1.333333333 Simplifying x = -1.333333333
| 9x+1=3x-1 | | 3(4+-2y)+4y=10 | | Y=-4/7x-1/7 | | 15x^2+40x-5=0 | | log(x)=0.40338 | | n^2-12n+21=0 | | e^8-9x=1168 | | 1/3(9)cubed | | 3/x-12/x-3=1 | | X^2+x+121=0 | | 230/360 | | 11/2×e=6 | | (2x+4)(2x+8)(x*x+4)=0 | | x^2-26y+169=0 | | 8x-12-3+3x-21=4.5 | | 4=0.5x+30 | | 30=0.5x+4 | | x(x+2)=7(x+x+2)+71 | | (2x+y)(3x+5y)= | | 15x^2+10=0 | | -4.5q+1.7=-25.8-2q | | 4x^2-23x-11=0 | | (b-8)/(8b-16) | | 8x-12+3x-21=4.5 | | S=5k+5vfork | | 4(1+3n)=8(n+5) | | 3p^2+10p+8=0 | | 8(1-4b)-(7b+8)=-4b-5b | | 233=33+x-22 | | 4x+3=68+x-1 | | 4p+5p+1=0 | | 8w-8+8=48+8 |